What increases the urban–rural gap in firm entry rates? - Kim, Younjun; Orazem, Peter (Small Business Economics, 2025)
Keywords: Agglomeration; Business; Economic geography; Economics; Entrepreneurship; Finance; Firm entry; Human capital; J24; M13; R11; Rural; Urban; dept.eco; peer-reviewed

Pre-play learning and the preference reversal phenomenon - Kim, Younjun; Hoffman, Elizabeth (Southern Economic Journal, 2018)
Elicited preference rankings for two lotteries are typically inconsistent across choice and pricing tasks. We test whether pre-play learning makes preference rankings consistent. Pre-play learning denotes ex-ante lottery learning, where subjects observe playing lotteries before making decisions. We find that pre-play learning makes the average selling prices for the p-bet, of subjects who choose the p-bet, higher than their average selling prices for the $-bet. However, pre-play learning is not strong enough to equalize the rates of standard and non-standard reversals, although pre-play learning reduces the rate of standard reversals.
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000450032400014 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: C91; D12; D81; dept.eco; peer-reviewed

Routine-biased technological change and declining employment rate of immigrants - Kim, Younjun; Thompson, Eric (Eastern Economic Journal, 2021)
We find that routine-biased technological change decreases the employment-to-population ratio of foreign-born population over the last three decades (1980–2010). This impact is greater for foreign-born population with lower English proficiency. As computerization and automation substitute for workers in routine occupations, switching from routine jobs to non-routine cognitive jobs may be more challenging for foreign-born workers than for native workers. © 2021, EEA.
2 citations (Crossref) [2023-10-31] https://experts.nebraska.edu/en/publications/routine-biased-technological-change-and-declining-employment-rate ; https://ideas.repec.org/a/pal/easeco/v47y2021i3d10.1057_s41302-021-00192-w.html
Keywords: dept.eco

Overconfidence and Public Intoxication Arrest: Evidence from a University Town Police Log - Hoffman, Elizabeth; Kim, Younjun (The B.E. Journal of Economic Analysis & Policy, 2022)
We show that overconfident individuals are likely to be arrested for public intoxication by using arrest records from a university town police log. This relationship is robust to various control variables such as risk aversion, time discounting, present bias, self-control, selfishness, loss aversion, and socializing with peers arrested for public intoxication. However, this relationship is no longer significant using only self-reported arrest data. We hypothesize that overconfident individuals are likely to underreport their arrests. This result has important implications for the use of self-reported data on public intoxication arrests rather than actual arrest records.
0 citations (Crossref) [2023-10-31]
Keywords: arrest; dept.eco; overconfidence; public intoxication

Broadband internet and new firm location decisions in rural areas - Kim, Younjun; Orazem, Peter F. (American Journal of Agricultural Economics, 2017)
55 citations (Crossref) [2023-10-31]
Keywords: dept.eco; peer-reviewed

Testing for Consistency in Firm Entry and Exit Between the National Establishment Time Series and Business Dynamics Statistics - Kim, Donghyuk; Kim, Younjun; Orazem, Peter; Thomas, Kelsey (Growth and Change, 2026)
Keywords: Business statistics; Census; Consistency (knowledge bases); Dynamics (music); Longitudinal data; Series (stratigraphy); Time series; dept.eco; entrepreneurship; entry; exit; firm data

Understanding Behavioral Explanations of the WTP-WTA Divergence Through a Neoclassical Lens: Implications for Environmental Policy - Kim, Younjun; Kling, Catherine; Zhao, Jinhua (Annual Review of Resource Economics, 2015)
The often observed empirical divergence between WTA and WTP measures of welfare change continues to be a topic of interest to both theoretical and applied economists. The divergence has particularly important implications for environmental policy. In this article, we review behavioral and other explanations of the disparity, with a focus on their connections to neoclassical welfare theory, and evaluate the empirical evidence of these explanations through the same lens. Some explanations of the disparity are consistent with neoclassical models, and some are not. Likewise, some imply that the divergences are attributed to underlying preferences (neoclassical or not), whereas others suggest that the divergences are due to elicitation methods, cognitive limitations, or other non-preference-related reasons. We argue that the source of the divergence can inform the choice of which measure, WTP or WTA, to use in a given empirical application.
Keywords: dept.eco

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
4 citations (Crossref) [2023-10-31] tex.ids: kwakGeneticallyModifiedCrops2020a
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

Does Agglomeration Matter Everywhere?: New Firm Location Decisions in Rural and Urban Markets - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F. (Journal of Regional Science, 2016)
We test whether commonly used measures of agglomeration economies encourage new firm entry in both urban and rural markets. Using new firm location decisions in Iowa and North Carolina, we find that measured agglomeration economies increase the probability of new firm entry in both urban and rural areas. Firms are more likely to locate in markets with an existing cluster of firms in the same industry, with greater concentrations of upstream suppliers or downstream customers, and with a larger proportion of college-educated workers in the local labor supply. Firms are less likely to enter markets with no incumbent firms in the sector or where production is concentrated in relatively few sectors. The same factors encourage both stand-alone start-ups and establishments built by multiplant firms. Commuting decisions exhibit the same pattern as new firm entry with workers commuting from low to high agglomeration markets. Because agglomeration economies are important for rural firm entry also, policies encouraging new firm entry should focus on relatively few job centers rather than encouraging new firm entry in every small town.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jors.12202
Keywords: dept.eco

Bilateral environmental aid under trade competition - Yoon, Sang; Kim, Younjun; Park, Byoung; Yoon, Chang-Ho (Applied Economics Letters, 2026)
Keywords: Bilateral environmental aid; Bilateral trade; Competition (biology); Environmental impact assessment; Environmental policy; Trade barrier; climate finance; dept.eco; energy-saving aid; strategic aid allocation; trade competition

Which Small Towns Attract Start-Ups and Why? Twenty Years of Evidence from Iowa - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F.; Han, Peter J. (American Journal of Agricultural Economics, 2021)
Using data on a sample of small Iowa towns consistently collected over two decades, we investigate how agglomeration economies, social capital, human capital, local fiscal policy, and natural amenities affect new firm entry. We find that human capital and agglomeration are more conducive to new firm entry than are natural amenities, local fiscal policy, or social capital. The impact of local fiscal policy is too small to overcome the locational disadvantages from insufficient endowment of human capital and agglomeration. A rural development approach that encourages firm entry in rural towns with the largest endowments of human capital and market agglomeration would be more successful than trying to raise firm entry in every town.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ajae.12144
Keywords: M13; R11; R39; agglomeration; dept.eco; firm location; human capital; peer-reviewed; rural

Bilateral environmental aid and trade - Yoon, Sang W.; Kim, Younjun; Park, Byoung G.; Yoon, Chang-Ho (Applied Economics, 2024)
The paper estimates the determinants of the growing volume of bilateral environmental aid for the mitigation of climate change using an empirically testable multilateral framework in which both donors and recipient countries compete in world export markets. As the potential donors weigh environmental benefits against the economic costs of providing aid, strategic interactions between the donors and the recipient countries as well as among the donors, influence the evolution of environmental aid. The paper shows that while the volume of bilateral environmental aid increases with the recipient country’s credible environmental commitment and bilateral trade volume, the competitive pressure in the export market reduces bilateral environmental aid. Free-riding incentives prevail among the individual donors, whereas the multilateral environmental aids that aim to restore the loss of global environmental resources without altering individual trade competitiveness can increase bilateral environmental aids.
_eprint: https://doi.org/10.1080/00036846.2023.2289935
Keywords: Environmental ODA; F18; F35; Q54; competitive threats; credible commitment; dept.eco; international trade; multilateral institutions; peer-reviewed